Latin American research in heart failure: visual and bibliometric analysis of the last 20 years - Batista Mendoza, Gisselle (2023)
Objective. To visually and bibliometrically analyze Latin  American research on heart failure in the last 20 years. Materials and methods. A bibliometric study using the Scopus database. A non-systematic search was carried out to collect data, which were analyzed using  Bibliometrix, a tool of the R programming language. Results. A total of 10204 documents were included in a period between 2003 to 2023. Of these, 66.9% (n=6824) corresponded to original articles, followed by review articles (15.5%; n=1583). International collaboration was present in 38.41% (n=3919) of the articles. Brazil stood out with the highest number of prolific authors and institutions (70% and 60%, respectively), consolidating its position as leader in the  region, followed by Argentina and Mexico. These countries also presented the papers with the highest impact and most outstanding metrics. Conclusions. This study identified a significant increase in heart failure research in Latin America over the last two decades, with Brazil, Argentina, and Mexico being the main drivers of this trend. Extensive and strong collaboration, mainly with high-income countries, appears to be critical to the momentum and the advancement of research in this area. Data systematization and resynchronization therapy are some of the topics of greatest interest at present.